2022
DOI: 10.3390/f13071118
|View full text |Cite
|
Sign up to set email alerts
|

Fire Damage to the Soil Bacterial Structure and Function Depends on Burn Severity: Experimental Burnings at a Lysimetric Facility (MedForECOtron)

Abstract: The soil microbiota is vulnerable to burning; however, it shows some resilience. No indices have yet been developed to assess fire damage related to soil biota. We evaluated the biological soil indices recorded by a Biolog EcoPlate System in a Mediterranean ecosystem. The experiment was carried out in an outdoor forest lysimeter facility (MedForECOtron), where we simulated burns with different burn severities. Burning increased the metabolic diversity of bacteria and most C-substrate utilization groups. Soil o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Forest fires' effects on the studied soil microorganisms are discussed below. Recent studies claim that fires can sterilize the soil [25,83,84]. The loss of these microorganisms not only affects biodiversity and interaction networks with plants or animals, but also their structures, such as filaments or biofilms, which are very relevant as adhesive agents aggregating particles and improving the soil structure [83][84][85].…”
Section: The Effect Of Fire On Soil Bacterial Communitymentioning
confidence: 99%
“…Forest fires' effects on the studied soil microorganisms are discussed below. Recent studies claim that fires can sterilize the soil [25,83,84]. The loss of these microorganisms not only affects biodiversity and interaction networks with plants or animals, but also their structures, such as filaments or biofilms, which are very relevant as adhesive agents aggregating particles and improving the soil structure [83][84][85].…”
Section: The Effect Of Fire On Soil Bacterial Communitymentioning
confidence: 99%
“…Furthermore, it is important to point out that fires are going to dramatically change the microbiota associated with the soil [ 27 , 28 , 29 ]. The loss of these microorganisms not only affects biodiversity and the networks of interactions with plants or animals, but also their structures, such as filaments or biofilms, that are very relevant as adhesive agents aggregating particles and improving the soil structure, as some authors reported for this region [ 9 , 29 , 30 ]. Hence, among the most common bacterial genera and species referenced in soils subject to different fire intensity, we can find Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…(as Pseudomonas fluorescens ), Arthrobacter spp., Burkholderia spp., Cohnella spp., Massilia spp., Blastococcus spp., Microvirga spp., Stenotrophomonas spp., Bacillus spp., and Clostridium spp. All these species are present in Mediterranean soils, and may serve in soil aggregation, as most of them are able to produce biofilms [ 27 , 28 , 29 , 30 , 31 , 32 ]. These microbial structures and activities can help in moisture retention [ 28 , 31 , 33 ], as well as help in nutrient cycling, critically influencing the availability of the main nutrients (fixing N, solubilizing P, K, S oxidizing) and micronutrients (siderophores and chelators for Mg, Ca, or Fe) for soil organisms and plants [ 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…China is also a country that suffers from wildfire. Wildfire, which causes significant damage to the ecological environment and socio-economic development, threatens the safety of people's lives and property and destroys surface vegetation and topsoil [2][3][4][5]. Therefore, timely and accurate wildfire detection is necessary for protecting the ecological environment and stabilizing the social economy.…”
Section: Introductionmentioning
confidence: 99%